PENGARUH GENDER, LATAR BELAKANG PEKERJAAN, DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK - Dewi Fitriyani; Eko Prasetyo; Reni Yustien; Achmad Hizazi (InFestasi, 2014)
The successful of implementation of the tax collection system and self assessment system have correlation with the characteristic of taxpayers. The characteristics of taxpayers can be seen from gender, occupation background and level of education. This research aims to proof empirically influence of gender, occupation and education to taxpayers’ compliance. The population in this research is individual taxpayers who has NPWP and registered in KPP Pratama Jambi City. The method of sampling uses nonprobability sampling with convenience sampling. The hypotheses are tested using analysis of variance (anova). Based on anova results, gender has no influence to taxpayers’ compliance, while occupation background and level of education has influence to taxpayers’ compliance in fulfilling tax obligations. In addition, there are also joint effect of gender, occupation background and level of education to taxpayers’ compliance.